Synthesis and Evaluation of Glucosyl-, Acyl- and Silyl- Resveratrol Derivatives as Retinoprotective Agents: Piceid Octanoate Notably Delays Photoreceptor Degeneration in a Retinitis Pigmentosa Mouse Model - Lourdes Valdés-Sánchez; Seyed Mohamadmehdi Moshtaghion; Estefanía Caballano-Infantes; Pablo Peñalver; Rosario Rodríguez-Ruiz; José Luis González-Alfonso; Francisco José Plou; Tom Desmet; Juan C. Morales; Francisco J. Díaz-Corrales (Pharmaceuticals)
Background: Retinitis pigmentosa (RP), the leading cause of inherited blindness in adults, is marked by the progressive degeneration of rod photoreceptors in the retina. While gene therapy has shown promise in treating RP in patients with specific mutations, no effective therapies currently exist for the majority of patients with diverse genetic backgrounds. Additionally, no intervention can yet prevent or delay photoreceptor loss across the broader RP patient population. Resveratrol (RES), a naturally occurring polyphenol, has shown cytoprotective effects in various neurodegenerative disease models; however, its therapeutic potential is limited by low bioavailability. Methods: In this study, we synthesized novel RES derivatives and assessed their retinoprotective effects in a murine model of RP (rd10 mice). Results: Among these derivatives, piceid octanoate (PIC-OCT) significantly delayed photoreceptor degeneration in the RP model, demonstrating superior efficacy compared to RES. Conclusions: PIC-OCT shows strong potential as a leading candidate for developing new therapeutic strategies for RP.